Paying lip service to gender inequality - EU rural development policy in Sweden - Pettersson, Katarina; Ahl, Helene; Berglund, Karin; Tillmar, Malin (Gender, place and culture : a journal of feminist geography, 2025)
While research has pointed to the lack of gender mainstreaming in rural and agricultural policy, how rural policy determines what is seen as problems of gender inequality in the first place and how it constructs men and women in relation to rural development remains unexplored. In this article we perform an in-depth analysis of how rural policy constructs gender inequality problems and gendered subjects. We employ the 'What's the problem represented to be' approach to analyse the implementation of the European Union's Rural Development Policy in one Swedish region, Jönköping County. We conclude that gender inequality is largely left unproblematic in relation to rural development, placing women in the subject position of being uninterested in rural development policy and lacking the ability to take it on. The focus on farmers and ICT broadband positions adult, Swedish-born men as the norm, reflecting a neoliberal emphasis on economic growth through competitive businesses. We also conclude that the policy twists 'gender mainstreaming' by claiming that it promotes gender equality, while it in fact takes no action. Paying lip service to gender equality rural policy thereby co-opts feminism, in line with a neoliberal 'postfeminist' discourse, which is harmful to the feminist project. Alternative approaches to gender inequalities suggest that there may be broader, and different, ways of discussing them in relation to rural development, making for a broader spectrum of problematisations and subject positions, which may, in turn, allow a transformation towards gender equality.